The unseen population of f- to k-type companions to hot subdwarf stars - Girven, J.; Steeghs, Danny T; Heber, Ulrich; Gaensicke, B. T.; Marsh, T. R.; Breedt, E.; Copperwheat, C. M.; Pyrzas, S.; Longa-Pena, P. (Monthly Notices of the Royal Astronomical Society, 2012)
We present a method to select hot subdwarf stars with A- to M-type companions using photometric selection criteria. We cover a wide range in wavelength by combining Galaxy Evolution Explorer (GALEX) ultraviolet data, optical photometry from the Sloan Digital Sky Survey (SDSS) and the Carlsberg Meridian Telescope, near-infrared data from Two-Micron All-Sky Survey (2MASS) and UKIDSS. We construct two complementary samples, one by matching GALEX, Carlsberg Meridian Catalogue (CMC) and 2MASS, as well as a smaller, but deeper, sample using GALEX, SDSS and UKIDSS. In both cases, a large number of composite subdwarf plus main-sequence star candidates were found. We fit their spectral energy distributions with a composite model in order to estimate the subdwarf and companion star effective temperatures along with the distance to each system. The distribution of subdwarf effective temperature was found to primarily lie in the 20000-30000K regime, but we also find cooler subdwarf candidates, making up ∼5-10percent. The most prevalent companion spectral types were seen to be main-sequence stars between F0 and K0, while subdwarfs with M-type companions appear much rarer. This is clear observational confirmation that a very efficient first stable Roche lobe overflow channel appears to produce a large number of subdwarfs with F- to K-type companions. Our samples thus support the importance of binary evolution for subdwarf formation. © 2012 The Authors Monthly Notices of the Royal Astronomical Society © 2012 RAS.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Infrared: stars; Stars: fundamental parameters; Subdwarfs; Ultraviolet: stars; White dwarfs